Developing a reflective practice in instructional design - Hartescu, Ioana (Proceedings of the International Conference on Networked Learning, 2012)
It is generally accepted as true that nobody is an expert from the very first try. However, most people expect that an adequate amount of years of experience result in building expertise. They may be right, especially if those years were spent not only acting and experimenting, but also reflecting on the actions and learning from these reflections. This study, grounded in the author’s everyday practice, is aiming to explore how instructional designers of online courses can be supported by using Web 2.0 tools to develop a reflective practice, and to form a community where they can exchange ideas, confront theories, identify problems and find solutions. The group is formed by people with backgrounds more or less connected to education, such as former trainers, school counsellors, psychologists, project managers, technical writers, graduates in public administration, etc. Having neither formal training in instructional design, nor experience in such a domain, they have no other choice than learn on the job. The approach taken is insider action research (AR), as the author has a responsibility concerning the work quality and productivity of instructional designers. Each AR cycle builds on the findings from the previous one, and enlarges the scale of the study while focusing the investigation. The pragmatic goal of the project is to succeed in building a community of practitioners that is autonomous, and has a core that is solid enough to integrate newcomers. The first action research cycle was exploratory and identified early issues of interest. The second cycle is currently in the analysis phase. The third cycle will run in 2012 based on the findings of the current one. The contribution this study seeks to make is to place knowledge about collective reflection, public vs. personal theories, and use of blogs as learning journals into the context of workplace learning and professional development with the goal to improve practice. Through this study, I aim to: (1) improve my understanding of the process of developing as a professional in the workplace, particularly on developing reflective skills, (2) analyse the impact of support actions and select the ones that facilitate the formation of a community of practice among instructional designers, and (3) identify potential differences of approach in offering and receiving support according to personal factors such as personal experience and other factors that may emerge.